Examining the potential for racial disparity in out-of-home placement decisions: A qualitative matched-pair study. (April 2017) - Skrypek, Margaret; Woodmass, Kyler; Rockymore, Maxie; Johnson, Geoff; Wells, Susan J.
Abstract: This community-based participatory research project was initiated following a charge from the Minnesota Legislature concerning the disproportionate representation of African American children in out-of-home care. The goal was to evaluate the impact of client race on child welfare worker decision-making and case outcomes and determine the potential for bias in decision-making. This report describes a detailed qualitative follow-up analysis of the data gathered for the quantitative inquiry. Cases of non-Hispanic, non-immigrant, white and African American children substantiated for child neglect in 2001 were identified from four Minnesota counties and followed until case closure or for at least 18 months. Cases were matched on type of neglect, gender, age group, and county. Cases of 81 pairs of black and white children were qualitatively coded and analyzed to identify possible race-linked differences in case characteristics, and which factors, including race, were most predictive of out-of-home placement decisions. In large part, the relevant facts of the case and risk to the child were clearly the driving force behind decisions made. However, models indicated that differences existed between race and age groups in incidence of certain case characteristics and in case process and outcomes, despite similar overall rates of referral for ongoing placement between races. Implications for future research are discussed, particularly the benefits of qualitative and quantitative data used in concert to contextualize findings. Highlights: The MN African American Disparities committee studied AA and white child placement. A qualitative study of ongoing child placement decisions followed 81 matched pairs. Various factors associated with placement by race counterbalanced one another. No CPS system-wide bias was identified in qualitative analysis.